OS ÓBITOS TEÓRICAMENTE EVITÁVEIS COMO CRITÉRIO DE AVALIAÇÃO DO TRABALHO SANITÁRIO - Ramos, Reinaldo (Arquivos da Faculdade de Higiene e Saúde Pública da Universidade de São Paulo, 1965)
After discussing the evaluation concepts and its crescent importance in public health practice, some critcria more frequentely used on evaluation and the difficulties of their application in underdeveloped areas, were appointed to dcmonstrate the deficiences of the structurc and of the operation of public health services. A criterion based on deaths estirnate rates, theoretically avoidable, was presented to be used in underdeveloped areas. Such criterion permits the identification of some evident fallacies and furnishes thc neccssary elcments to a minimal activities programa in the public health practice. This criterion is applied to the City of São Paulo, bascd on obituary of 1963 as a demonstration.